Identifying Farmer Workplace Injury Risk Factors in Ireland Using Farm Accounts Data. Issue 4 (2nd October 2021) - McNamara, John; Kinsella, Anne; Osborne, Aoife; Blake, Catherine; Meredith, David; Kinsella, James
ABSTRACT: Identification of occupational workplace injury risk factors is dependent on gaining sufficient and reliable data on both injury occurrence and associated workplace factors. Assessing workplace injury risk factors associated with farming is challenged by non-collection, non-reporting, or under-reporting by farmers, particularly those operating family farms in a self-employed manner. A supplementary (or add-on) farm operator (FO) workplace injury survey was undertaken in association with the Irish National Farm Survey (NFS), which is responsible for provision of Irish farm-level data to the European Commission (EC) Farm Accountancy Data Network (FADN). Data from this add-on survey were analyzed in association with farm and socio-economic data routinely collected by NFS as a component of the FADN. The combined data-set was analyzed using both descriptive and inferential statistical techniques including multivariate logistic regression to identify risk factors for occurrence of farm operator workplace injuries (FOWI). FOWI levels were significantly higher on farms where both the FO and their spouse engaged in Off Farm Employment (OFE). More generally, FO injury levels were associated with farm workload and investment levels. The study demonstrates how FADN farm and socio-economic data can be combined with additional FO workplace injury data to identify workplace injury risk factors. The study identifies a risk factor for FOWI occurrence where both FO and spouse engaged in OFE. More generally, it indicates that farm workplace injuries are associated with farm management-related factors.